Development and Evaluation of Elementary Osmotic Pump for the Simultaneous Delivery of Nifedipine and Metoprolol Tartrate - Kumaravelrajan, Rajagopal (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: A system that can deliver multidrugs at a controlled rate is very important to the treatment of various chronic diseases such as diabetes, asthma, and hypertension. In general, both highly and poorly water-soluble drugs are not good candidates for elementary osmotic delivery, so in the present investigation nifedipine-hydroxyproyl-Î²-cyclodextrin (1:1) inclusion complex was used to modulate the solubility of nifedipine (NP) within the core and metoprolol was used not only as the active ingredient but also as osmotic agent. Materials and Methods: NP-cyclodextrin complex was prepared by coprecipitation method. The tablets were prepared and coated with cellulose acetate phthalate-containing dibutyl phthalate as plasticizer at various concentrations. The coated tablets drilled for orifice. The orifice size, level of plasticizer, and coating thickness were used as formulation variables. Finally, the optimized formulation was studied for different pH, agitational speed, and release mechanism. The optimized formulation was also subjected to in vivo prediction for the desired Cmax and Cmin using superposition method. Results: Formulation variables such as orifice size, level of plasticizer, and coat thickness of semipermeable membrane were found to affect the drug release from the developed formulations. The optimal elementary osmotic pump was found to deliver both drugs at a rate of approximately zero order for up to 10 h independent of pH and agitational intensity but dependent on the osmotic pressure of the release media. Conclusion: Hence, the prototype design of the system could be applied to other combinations of drugs used for cardiovascular diseases, diabetes, etc.